Synthesis, Antibacterial and Antifungal Activities of Some Novel Derivatives of Thiazolo[2,3-b]dihydropyrimidine Possessing 4-Pyrazolyl Moiety - J. Solanki, Manish; Shah, V.H. (Asian Journal of Chemistry, 2012)
A series of new 2-arylidene-5-(5-chloro-3-methyl-1-N-phenyl-pyrazol-4-yl)-6-carbethoxy-7- methyl-5H-thiazolo[2,3-b]pyrimidin-3(1H)-ones have been synthesized by a three component (MCR) reaction involving 4-(5-chloro-3-methyl-1-N-phenyl- pyrazol-4-yl)-5-carbethoxy-6- methyl-3,4-dihydropyrimidin-2(1H)-thione, monochloroacetyl chloride and aryl aldehydes. The newly synthesized compounds were well characterized by elemental analysis, IR, 1H NMR and mass spectral studies. The newly synthesized compounds were screened for their antibacterial and antifungal activities and have exhibited moderate to excellent growth inhibition of bacteria and fungi.